PROFESIONALISME KERJA DA'I (Tinjauan Teoritis Dalam Manajemen Publik) - yummil Hasan (Universitas Islam Negeri Imam Bonjol Padang, 2007)
These days, discussion about public management specially about human resource get focus from various circle as key determining in the effort realizing the target of which will reach. In this time human resource is progresshvely claimed its ability to execute duties in place environntent work In this case, da'i is to represent top- drawer human resource, in effort to reach eficacy. Human resource or of da'i this can support organization with masterpiece talent motivation and creativity After all as perfect as economic and technological aspect, withoit difficult human being aspect presumably the targets can reach Pursuant to fact of empiric in field stand-out that a da'i owning high fob professionalism will be impetuous and mean business to work and they will be ord for gve best masterpiece in the form of high labour capacity in its service of him to public On the contrary, a da'i which do not have job professionalism hence he will eften conduct mistake of job because he do not have adequate skill and knowledge and also altruism attitude utilize to upport execurion of its duty